PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA - Silaban, Dewi Hariani; Siregar, Dina Arfianti; Safrida, Eli; Napitupulu, Ilham Hidayah (Jurnal Riset Terapan Akuntansi, 2025)
This study was conducted to examine the effect of good corporate governance and corporate social responsibility on the financial performance of companies. The dependent variable in this research is financial performance, which is measured using Return on Assets (ROA). The independent variables include independent commissioners, the board of directors, the audit committee, managerial ownership, institutional ownership, and corporate social responsibility. This research uses secondary data obtained from annual reports and sustainability reports of mining sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The sample consists of 18 companies, resulting in a total of 72 observations selected using the purposive sampling method. Data analysis was carried out using multiple linear regression with the assistance of SPSS version 26. The results show that institutional ownership has a significant effect on financial performance, as higher institutional ownership provides stronger control over management and encourages more rational and efficient decision-making. Meanwhile, independent commissioners, the board of directors, the audit committee, managerial ownership, and corporate social responsibility do not have a significant effect on financial performance. Keywords: Kinerja Keuangan, Good Corporate Governance and Corporate Social Responsibilitity